EVALUASI KELAYAKAN PROYEK DAN PERANKINGAN AREA PROSPEK PANAS BUMI KANDIDAT LOKASI PROGRAM GOVERNMENT DRILLING: EVALUATION OF FEASIBILITY AND RANKING OF GEOTHERMAL PROSPECT AREA CANDIDATES FOR GOVERNMENT DRILLING PROGRAM LOCATIONS - Nugraha, Husin Setia; Wildan, Dadan; Rina Wahyuningsih (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
Government drilling is a geothermal exploration well drilling program carried out by the government. For planning, it is necessary to rank candidate prospect areas to be included in the program. This study ranked twenty candidate drilling sites using the incremental internal rate of return or incremental IRR method from discounted cash flow (DCF) calculations. The stages for the method are calculating project value and feasibility based on profitability parameters in each prospect area and calculating and ranking based on incremental IRR. As a result, based on the value of the profitability parameter, only two candidate areas for the program are feasible based on the project's IRR and NPV values, namely Nage and Mount Galunggung. Meanwhile, based on the BCR value, in addition to those two locations, two prospect areas are categorized as feasible, namely Bittuang and Mount Papandayan. Thus, Nage and Mount Galunggung are financially viable, and Bittuang and Mount Papandayan are economically viable. Improving the financial viability of Bittuang and Gunung Papandayan requires other fiscal incentives. For ranking, the results based on incremental IRR calculations and IRR result in the same order for the top four or the viable projects. The same results are because of their homogeneous project type, which is a geothermal project. Based on the results of this study, it is recommended to re-evaluate candidate prospect area locations for the program. It is because out of twenty candidate locations, only two are financially viable, and four are economically viable. Choosing the right location is one of the keys to the success of this program.